Effects of PARP-1 Deficiency and Histamine H4 Receptor Inhibition in an Inflammatory Model of Lung Fibrosis in Mice - Durante, Mariaconcetta; Sgambellone, Silvia; Lanzi, Cecilia; Nardini, Patrizia; Pini, Alessandro; Moroni, Flavio; Masini, Emanuela; Lucarini, Laura (Frontiers in Pharmacology, 2019)
Pulmonary fibrosis is the most frequent form of interstitial lung disease. Effective therapies are not yet available; novel therapeutic approaches are needed for counteracting fibrosis. Poly(ADP-ribose) polymerase is a family of enzymes, involved in DNA repair and cell apoptosis. PARP-1 deficient mice exhibited reduced lung fibrosis in response to bleomycin treatment compared to wild-type controls. Histamine H4 receptors (H4Rs) have been identified as a new target for inflammatory and immune disorders and H4R ligands reduced inflammation and oxidative stress in lung tissue. The aim of the study was to evaluate the involvement of PARP-1 in H4R signaling pathway in a model of bleomycin-induced lung fibrosis in PARP-1-/- and WT mice. Animals were treated with bleomycin or saline by intra-tracheal injection. JNJ7777120, an H4R antagonist, or VUF8430, an H4R agonist, were administered i.p for 21 days. Airway resistance to inflation was evaluated and lung tissues were processed for PARylated protein content, oxidative stress evaluation and histology of small bronchi. The levels of pro-inflammatory (IL-1β and TNF-α), regulatory (IL-10) and pro-fibrotic (TGF-β) cytokines were evaluated. The deposition of αSMA was determined by immunofluorescence analysis. The results indicate that JNJ7777120 reduces PARylated protein production, decreases oxidative stress damage and MPO, a marker for leukocyte tissue infiltration, in PARP-1-/- mice. A significant decrease in the production of both IL-1β and TNF-α and a significant increase in IL-10 levels are observed in mice treated with H4R antagonist, suggesting a crucial anti-inflammatory activity of JNJ7777120. The smooth muscle layer thickness, the goblet cell relative number and collagen deposition decreased following JNJ7777120 administration. The H4R antagonist treatment also reduces TGF-β production and αSMA deposition, suggesting an important role of JNJ7777120 in airway remodeling. Our results show that PARylation is essential for the pathogenesis of pulmonary fibrosis and propose that PARP-1 and H4Rs are both involved in inflammatory and fibrotic responses. JNJ7777120 treatment, in a condition of PARP-1 inhibition, exerts anti-inflammatory and anti-fibrotic effects, reducing airway remodeling and bronchoconstriction. Therefore, selective inhibition of H4Rs together with non-toxic doses of selective PARP-1 inhibitors could have clinical relevance for the treatment of idiopathic pulmonary fibrosis.